Angiotensin (1–7) Expressing Probiotic as a Potential Treatment for Dementia - Hernandez, Abbi R.; Banerjee, Anisha; Carter, Christy S.; Buford, Thomas W. (Frontiers in Aging, 2021)
Increasing life expectancies are unfortunately accompanied by increased prevalence of Alzheimer’s disease (AD). Regrettably, there are no current therapeutic options capable of preventing or treating AD. We review here data indicating that AD is accompanied by gut dysbiosis and impaired renin angiotensin system (RAS) function. Therefore, we propose the potential utility of an intervention targeting both the gut microbiome and RAS as both are heavily involved in proper CNS function. One potential approach which our group is currently exploring is the use of genetically-modified probiotics (GMPs) to deliver therapeutic compounds. In this review, we specifically highlight the potential utility of utilizing a GMP to deliver Angiotensin (1-7), a beneficial component of the renin-angiotensin system with relevant functions in circulation as well as locally in the gut and brain.